2000
DOI: 10.1177/105065190001400201
|View full text |Cite
|
Sign up to set email alerts
|

Strength in the Technical Communication Journals and Diversity in the Serials Cited

Abstract: More than 1,600 serials from across the disciplines were identified as sources for technical communication scholars. The 99 most frequently cited serials are described. This citation analysis is distinguished from others by the size of the database (25,000+ citations), the 10-year review of articles published in five technical communication journals between 1988 and 1997, the number of serials cited and reviewed, and the focus on technical communication as a discipline. The analysis yielded two observations. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The ABC Publications Board believes that we have limited collective knowledge about the impact that external perceptions of journal quality have on our discipline and about our own views, though somewhat related research appeared some time ago (Krapels & Martin, 1998;Reinsch & Lewis, 1993;Reinsch & Reinsch, 1996;Smith, 2000). Meanwhile, a significant change seems to be occurring in assessing journal quality.…”
Section: • Business Communication Academics At Asian and European Unimentioning
confidence: 99%
“…The ABC Publications Board believes that we have limited collective knowledge about the impact that external perceptions of journal quality have on our discipline and about our own views, though somewhat related research appeared some time ago (Krapels & Martin, 1998;Reinsch & Lewis, 1993;Reinsch & Reinsch, 1996;Smith, 2000). Meanwhile, a significant change seems to be occurring in assessing journal quality.…”
Section: • Business Communication Academics At Asian and European Unimentioning
confidence: 99%
“…Our goals in this study were to build on Smith's (2000aSmith's ( , 2000b 20-year-old citation analyses to learn where the TC academy-industry divide is most and least divergent and what those divisions mean for the overall health of the field of TC. Although some of these divisions could be attributed to differing nomenclature emphases (e.g., perhaps academics emphasize audience analysis whereas practitioners emphasize user and task analysis), we believe that the results of this study, which suggest uneven priorities between practitioners and academics, is a potential harbinger of rockiness in the discipline.…”
Section: Discussionmentioning
confidence: 99%
“…But the topics covered in TC have been less studied and have denied the field opportunities for a "more holistic understanding of where technical communication has been, where the field is now, and where the field could go" (Boettger & Friess, 2020). Some of the first examinations of the scholarly journal content of TC were Smith's citation analyses (Smith, 2000a(Smith, , 2000b. These analyses reveal that content areas in the research journals were "broadly identified as professional issues (defining technical communication, pedagogy, and research methods), rhetoric and the rhetorics of communities, document design and technology issues, and workplace communication" (Smith, 2000a, p. 427).…”
Section: Content Areasmentioning
confidence: 99%
See 2 more Smart Citations